The effectiveness of classic lecture and workshop as interventions to improve primary health care providers knowledge and skill on the management of pediatric emergencies: a case study - Ricky Indra Alfaray; Rahmat Sayyid Zharfan; Yudhistira Pradnyan Kloping; Yudith Annisa Ayu Rezkitha; Rafiqy Sa’adiy Faizun; Saruuljavkhlan Batsaikhan; Ahmad Siddiq Muhajir; Bestya Presidiana; Umaimah Rosyidah; Khodijah Nidaul Chasanah; Delia Nur Aini; Naufal Fauzy; Kamal Musthofa; Nur Firdaos; Samsriyaningsih Handayani (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
Abstract A preliminary study showed that most health workers in primary health care (PHC) claimed that they need a refreshing course because of their lack of updated knowledge and skill. This study enrolled 27 primary healthcare workers recruited from the PHC. The intervention used were classic lectures and workshops. The knowledge was evaluated using a paper-based test and practice, while the skill was evaluated using a practice test. Multiple questions (pre-test and post-test) based on current emergency management for pediatric were used for paper-based evaluation. Semi-structured interviews were conducted to confirm the subject's perspective on the intervention. A paired t-test was used for evaluating the pre- and post-test results, which was confirmed by a triangulation approach. There was a significant difference between the pre- and post-test results (p<0.001), and 8 of 10 subjects can demonstrate the procedure learned correctly after the intervention. A total of 14 interviewed subjects stated great effectiveness of the intervention, with several limitations on applicability in daily clinical practice. Classic lecture and workshop as an intervention in health education effectively increase health workers' knowledge and skill in PHC. This study might help other rural areas PHC apply the same method so the professionalism and quality of health workers in PHC providers can be maintained.Keywords                : primary health care, classic lecture; workshop; knowledge; skillCorrespondence     : rickyindraalfaray@gmail.com